Electrolyte and preparation method of electrolytic copper foil for lithium battery

The copper ion electrodeposition behavior is adjusted through the ratio of specific additives to form a dense structure, which solves the contradiction between the thinning of the electrolytic copper foil and the high tensile strength, and improves the performance of lithium batteries.

CN120366861AActive Publication Date: 2025-07-25GUANGDONG FINE YUAN SCI TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510506377.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-25
Estimated Expiration
2045-04-22

AI Technical Summary

Technical Problem

The existing electrolytic copper foil manufacturing technology is difficult to improve tensile strength while maintaining thinning, limiting the application performance of lithium batteries.

Method used

By selecting a specific proportion of brighteners, high antigens, stabilizers and wetting agents, the electrodeposition behavior of copper ions is coordinated to form a dense structure, and the tensile strength and ductility of the copper foil are improved.

Benefits of technology

The tensile strength of electrolytic copper foil is greater than 700MPa and elongation is greater than 5.0%, solving the problems of easy breakage and poor durability of copper foil, and improving the charging and discharge life and safety performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005369903450000031
    Figure BDA0005369903450000031
  • Figure BDA0005369903450000041
    Figure BDA0005369903450000041
  • Figure BDA0005369903450000071
    Figure BDA0005369903450000071
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to an electrolyte and a preparation method of an electrolytic copper foil for a lithium battery. The electrolyte comprises the following components: 105-120 g / L of sulfuric acid, 15-120 mg / L of a brightener, 10-60 mg / L of gelatin, 3-50 mg / L of a high resistance agent, 5-55 mg / L of a stabilizer, 1-15 mg / L of a wetting agent, 10-30 mg / L of Cl, and the balance of water. The tensile strength of the copper foil can be remarkably improved while the thickness of the copper foil is reduced, the tensile strength is larger than 700 MPa, and the ductility is larger than 5.0%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and specifically, to an electrolyte and a preparation method of an electrolytic copper foil for a lithium battery. Background Art

[0002] As a core component of electric vehicles, consumer electronics, and energy storage systems, the performance and safety of lithium batteries highly depend on technological breakthroughs in key materials. Among them, electrolytic copper foil, as the core material of the negative electrode current collector, undertakes dual functions in the battery by virtue of its excellent electrical conductivity, corrosion resistance, and mechanical stability: it is both a carrier of the negative electrode active material and a key channel for electron transmission. With the upgrading of the market's demand for high energy density and high safety, electrolytic copper foil is evolving towards the coordinated development of ultra-thinness and high tensile strength. However, the existing electrolytic copper foil manufacturing technology is difficult to improve the tensile strength while maintaining thinness, thus limiting the application performance of lithium batteries.

[0003] Chinese invention patent CN118292056 B discloses an electrolytic copper foil for a lithium battery, its preparation method, and application. By coordinating and controlling the proportion of additives and various parameters in the process steps, the internal stress of the electrolytic copper foil can be removed in advance, enabling the grains to be evenly and densely distributed, avoiding high warpage of the electrolytic copper foil and fracture of the electrolytic copper foil caused by subsequent heat sources or deformations, and having high thermal stability, but the tensile strength and elongation are still not high enough. Summary of the Invention

[0004] The first aspect of the present invention provides an electrolyte, including components with the following concentrations: sulfuric acid 105 - 120 g / L, brightener 15 - 120 mg / L, gelatin 10 - 60 mg / L, high resistance agent 3 - 50 mg / L, stabilizer 3 - 55 mg / L, wetting agent 1 - 15 mg / L, Cl - 10 - 30 mg / L, and water to make up the balance.

[0005] Optionally, the Cl - is provided by hydrochloric acid.

[0006] The brightener includes sodium thiazolinyl dithiopropane sulfonate, sodium polydithiodipropane sulfonate, and 3 - mercapto - 1 - propane sulfonate, and the weight ratio of sodium thiazolinyl dithiopropane sulfonate, sodium polydithiodipropane sulfonate, and 3 - mercapto - 1 - propane sulfonate is 1:(0.8 - 1.2):(1.2 - 2).

[0007] Optionally, the weight ratio of sodium thiazolinyl dithiopropane sulfonate, sodium polydithiodipropane sulfonate, and 3 - mercapto - 1 - propane sulfonate is 1:(0.8 - 1.2):(1.4 - 2).

[0008] By selecting specific brighteners and their ratios, the tensile strength of the copper foil can be improved. Sodium thiazolinyl dithiopropane sulfonate promotes grain refinement, sodium polydithiopropane sulfonate inhibits the copper deposition rate, and sodium 3-mercapto-1-propane sulfonate enhances surface flatness. By their synergistic effect, the electrodeposition behavior of copper ions is regulated to avoid coarse grains. In particular, a thiol compound in a specific ratio promotes uniform nucleation by adsorbing on the cathode surface, balancing the deposition rate and the grain refinement effect, reducing defects, forming a dense structure, and enhancing surface flatness, thereby improving the tensile strength.

[0009] The high-resistance agent includes Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt, and thiourea, and the weight ratio of Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt, and thiourea is 1:(0.8 - 1.2):(1 - 2):(1.8 - 3).

[0010] Optionally, the weight ratio of Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt, and thiourea is 1:(0.8 - 1.2):(1 - 2):(1.8 - 2.5).

[0011] By selecting specific high-resistance agents and their ratios, the tensile strength of the copper foil can be further increased to be greater than 700 MPa. It may be the combination of Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt, and thiourea that jointly balance the charge distribution and adsorption passivation and form a complex with copper ions to inhibit dendrite growth. Polyquaternary ammonium salt and polyethyleneimine avoid the disordered deposition of copper ions by adsorbing on the cathode surface. At the same time, they cooperate with the grain refinement effect of the brightener to avoid the phenomenon of too low deposition rate caused by excessive inhibition, thereby forming a fine and uniform grain structure and further enhancing the tensile strength.

[0012] The stabilizer includes 3-methyltetrahydrothiazole-2-thione and 2-mercaptothiazoline, and the weight ratio of 3-methyltetrahydrothiazole-2-thione and 2-mercaptothiazoline is (0.5 - 1.8):1.

[0013] Optionally, the weight ratio of 3-methyltetrahydrothiazole-2-thione and 2-mercaptothiazoline is (0.8 - 1.5):1.

[0014] The wetting agent includes polyethylene glycol with a number-average molecular weight of 600 - 2000 Da and polyethylene glycol with a number-average molecular weight of 4000 - 8000 Da.

[0015] The weight ratio of polyethylene glycol with a number-average molecular weight of 600 - 2000 Da and polyethylene glycol with a number-average molecular weight of 4000 - 8000 Da is 1:(0.6 - 1.5).

[0016] Optionally, the weight ratio of the polyethylene glycol with a number average molecular weight of 600-2000Da to the polyethylene glycol with a number average molecular weight of 4000-8000Da is 1:(0.6-1.2).

[0017] By selecting specific stabilizers, wetting agents and their ratios, the elongation can be further improved at high tensile strength. Specific stabilizers and their ratios balance the pH stability and antioxidant requirements, meeting the stability in a high acidity environment. Specific wetting agents and their ratios synergistically reduce the contact angle between the electrolyte and the cathode roller, ensuring uniform deposition of copper ions, reducing bubbles and pores, and matching the electrolysis process with high current density to avoid uneven deposition caused by insufficient local wetting. Specific stabilizers maintain the stability of the electrolyte components, and wetting agents ensure uniform deposition. Together, they reduce microscopic defects and thus improve elongation.

[0018] The weight average molecular weight of the gelatin is 10000-20000 Da.

[0019] The second aspect of the present invention provides a method for preparing electrolytic copper foil for lithium batteries, comprising the following steps: dissolving copper wire in the electrolyte and conveying the copper wire to a foil making machine for electrolytic foil making.

[0020] During the electrolysis, Cu 2+ The content is 80-110g / L.

[0021] Optionally, the electrolyte contains Cu 2+ The content is 80-100g / L.

[0022] The temperature of the electrolyte is 50-65°C.

[0023] Optionally, the temperature of the electrolyte is 50-60°C.

[0024] The transport flow rate is 50-70m 3 / h.

[0025] Optionally, the transport flow rate is 50-60m 3 / h.

[0026] The current density of the electrolysis is 3600-6000A / m 2 .

[0027] Optionally, the current density of the electrolysis is 4000-6000A / m 2 .

[0028] Beneficial Effects

[0029] 1. By selecting a specific brightener and its ratio, the tensile strength of copper foil can be improved.

[0030] 2. By selecting specific high-resistance agents and their ratios, the tensile strength of the copper foil can be further increased to be greater than 700 MPa.

[0031] 3. By selecting specific stabilizers, wetting agents and their ratios, the elongation rate can be further increased under high tensile strength.

[0032] 4. Through the synergistic effect among various additives, the copper foil can have excellent tensile strength and elongation rate simultaneously.

[0033] 5. The present invention solves the problems of easy fracture and poor durability of copper foil in the prior art, thereby improving the charge and discharge life and safety performance of lithium batteries. Specific Embodiments

[0034] The raw materials used in the following examples and comparative examples are shown in Table 1, and the components not listed do not limit the manufacturers:

[0035] Table 1

[0036]

[0037]

[0038] Example 1

[0039] An electrolyte is composed of components with the following concentrations: sulfuric acid 110 g / L, brightening agent 68 mg / L, gelatin 35 mg / L, high-resistance agent 27 mg / L, stabilizer 30 mg / L, wetting agent 7 mg / L, Cl - 20 mg / L, and water makes up the balance; the Cl - is provided by hydrochloric acid.

[0040] The brightening agent is sodium thiazolinyl dithiopropane sulfonate, sodium polydithiodipropane sulfonate and 3-mercapto-1-propane sulfonate, and the weight ratio of sodium thiazolinyl dithiopropane sulfonate, sodium polydithiodipropane sulfonate and 3-mercapto-1-propane sulfonate is 1:1:1.5.

[0041] The high-resistance agent is Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt and thiourea, and the weight ratio of Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt and thiourea is 1:1:1.5:2.

[0042] The stabilizer is 3-methyltetrahydrothiazole-2-thione and 2-mercaptothiazoline, and the weight ratio of 3-methyltetrahydrothiazole-2-thione and 2-mercaptothiazoline is 1:1.

[0043] The wetting agent includes polyethylene glycol with a number average molecular weight of 1000 Da and polyethylene glycol with a number average molecular weight of 4000 Da, and the weight ratio of the polyethylene glycol with a number average molecular weight of 1000 Da to the polyethylene glycol with a number average molecular weight of 4000 Da is 1:0.9.

[0044] A method for preparing an electrolytic copper foil for a lithium battery comprises the following steps: dissolving copper wire in the electrolyte described above and transporting it to a foil making machine for electrolytic foil making.

[0045] During electrolysis, the Cu content in the electrolyte 2+ is 90 g / L; the temperature of the electrolyte is 56 °C; the flow rate of the transportation is 55 m 3 / h; the current density of the electrolysis is 5000 A / m 2 .

[0046] Example 2

[0047] The specific implementation method is the same as that of Example 1; the difference is that the temperature of the electrolyte is 50 °C.

[0048] Example 3

[0049] The specific implementation method is the same as that of Example 1; the difference is that the flow rate of the transportation is 50 m 3 / h.

[0050] Example 4

[0051] The specific implementation method is the same as that of Example 1; the difference is that the temperature of the electrolyte is 60 °C; the current density of the electrolysis is 4000 A / m 2 .

[0052] Example 5

[0053] The specific implementation method is the same as that of Example 1; the difference is that the flow rate of the transportation is 60 m 3 / h.

[0054] Example 6

[0055] The specific implementation method is the same as that of Example 1; the difference is that the current density of the electrolysis is 6000 A / m 2 ; sulfuric acid 110 g / L.

[0056] Example 7

[0057] The specific implementation method is the same as that of Example 1; the difference is that during electrolysis, the Cu content in the electrolyte 2+ is 100 g / L; gelatin 10 mg / L.

[0058] Example 8

[0059] The specific implementation method is the same as that of Example 1; the difference is that the sulfuric acid is 120 g / L.

[0060] Example 9

[0061] The specific implementation method is the same as that of Example 1; the difference is that the gelatin is 60 mg / L and Cl⁻ is 10 mg / L.

[0062] Example 10

[0063] The specific implementation method is the same as that of Example 1; the difference is that the brightener is 15 mg / L.

[0064] Example 11

[0065] The specific implementation method is the same as that of Example 1; the difference is that Cl⁻ is 30 mg / L and the high resistance agent is 3 mg / L.

[0066] Example 12

[0067] The specific implementation method is the same as that of Example 1; the difference is that the brightener is 120 mg / L and the stabilizer is 3 mg / L.

[0068] Example 13

[0069] The specific implementation method is the same as that of Example 1; the difference is that the high resistance agent is 50 mg / L and the wetting agent is 1 mg / L.

[0070] Example 14

[0071] The specific implementation method is the same as that of Example 1; the difference is that the stabilizer is 55 mg / L.

[0072] Example 15

[0073] The specific implementation method is the same as that of Example 1; the difference is that the wetting agent is 15 mg / L.

[0074] Comparative Example 1

[0075] The specific implementation method is the same as that of Example 1; the difference is that no brightener is added.

[0076] Comparative Example 2

[0077] The specific implementation method is the same as that of Example 1; the difference is that no high resistance agent is added.

[0078] Comparative Example 3

[0079] The specific implementation method is the same as that of Example 1; the difference is that no stabilizer is added.

[0080] Comparative Example 4

[0081] The specific implementation method is the same as that of Example 1; the difference is that no wetting agent is added.

[0082] Comparative Example 5

[0083] The specific implementation manner is the same as that of Example 1; the difference is that gelatin is not added.

[0084] Comparative Example 6

[0085] The specific implementation manner is the same as that of Example 1; the difference is that the Cl- is 40 mg / L.

[0086] Comparative Example 7

[0087] The specific implementation manner is the same as that of Example 1; the difference is that the temperature of the electrolyte is 48 °C.

[0088] Comparative Example 8

[0089] The specific implementation manner is the same as that of Example 1; the difference is that the flow rate of the transportation is 40 m 3 / h.

[0090] Comparative Example 9

[0091] The specific implementation manner is the same as that of Example 1; the difference is that the current density of the electrolysis is 3500 A / m 2 .

[0092] Comparative Example 10

[0093] The specific implementation manner is the same as that of Example 1; the difference is that the content of Cu in the electrolyte during electrolysis 2+ is 75 g / L.

[0094] Comparative Example 11

[0095] The specific implementation manner is the same as that of Example 1; the difference is that the sulfuric acid is 100 g / L.

[0096] Comparative Example 12

[0097] The specific implementation manner is the same as that of Example 1; the difference is that the weight ratio of sodium thiazolinyl dithiopropane sulfonate, sodium polydithiopropane sulfonate and sodium 3-mercapto-1-propane sulfonate is 1:1:1.

[0098] Comparative Example 13

[0099] The specific implementation manner is the same as that of Example 1; the difference is that sodium 3-(benzimidazole-2-ylthio)-propane sulfonate is used instead of sodium 3-mercapto-1-propane sulfonate.

[0100] Comparative Example 14

[0101] The specific implementation manner is the same as that of Example 1; the difference is that the weight ratio of Janus green B, polyethyleneimine alkyl salt, hexylbenzylamine salt and thiourea is 1:1:1:1.5:.

[0102] Comparative Example 15

[0103] The specific implementation manner is the same as that of Example 1; the difference is that diethylpropiolylamine is used instead of polyethyleneimine alkyl salt.

[0104] Comparative Example 16

[0105] The specific implementation manner is the same as that of Example 1; the difference is that the weight ratio of 3-methyltetrahydrothiazole-2-thione to 2-mercaptothiazoline is 2:1.

[0106] Comparative Example 17

[0107] The specific implementation manner is the same as that of Example 1; the difference is that 2-methyl-4-isothiazolin-3-one is used instead of 3-methyltetrahydrothiazole-2-thione.

[0108] Comparative Example 18

[0109] The specific implementation manner is the same as that of Example 1; the difference is that the weight ratio of polyethylene glycol with a number average molecular weight of 1000 Da to polyethylene glycol with a number average molecular weight of 4000 Da is 2:1.

[0110] Performance test method

[0111] Copper foils with a thickness of 6 microns were prepared according to the methods in the examples and comparative examples. Referring to the test methods in GB / T29847-2013, the tensile strength and elongation of the copper foils were tested, and the test data are listed in Table 2.

[0112] Performance test data

[0113] Table 2

[0114]

[0115]

Claims

1. An electrolyte, characterized in that, Comprising components in the following concentrations: sulfuric acid 105 - 120 g / L, brightener 15 - 120 mg / L, gelatin 10 - 60 mg / L, high resistance agent 3 - 50 mg / L, stabilizer 3 - 55 mg / L, wetting agent 1 - 15 mg / L, Cl - 10 - 30 mg / L, and water to make up the balance.

2. The electrolyte according to claim 1, wherein The brightening agent includes sodium thiazolinyl dithiopropane sulfonate, sodium polydithiopropane sulfonate and 3-mercapto-1-propane sulfonate, and the weight ratio of sodium thiazolinyl dithiopropane sulfonate, sodium polydithiopropane sulfonate and 3-mercapto-1-propane sulfonate is 1: (0.8-1.2):(1.2-2)。 3. The electrolyte according to claim 1, wherein The high resistance agent includes Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt and thiourea, and the weight ratio of Janus green B, polyethyleneimine alkyl salt, hexyl benzyl amine salt and thiourea is 1:(0.8 - 1.2):(1 - 2):(1.8 - 3).

4. The electrolyte according to claim 1, characterized in that, The stabilizer includes 3-methyltetrahydrothiazole-2-thione and 2-mercapto thiazoline, and the weight ratio of 3-methyltetrahydrothiazole-2-thione and 2-mercapto thiazoline is (0.5 - 1.8):

1.

5. The electrolyte according to claim 1, characterized in that, The wetting agent includes polyethylene glycol with a number average molecular weight of 600 - 2000 Da and polyethylene glycol with a number average molecular weight of 4000 - 8000 Da.

6. The electrolyte according to claim 1, wherein The weight ratio of polyethylene glycol with a number average molecular weight of 600 - 2000 Da and polyethylene glycol with a number average molecular weight of 4000 - 8000 Da is 1:(0.6 - 1.5).

7. A preparation method of an electrolytic copper foil for a lithium battery, characterized in that, It includes the following steps: Dissolve the copper wire in the electrolyte solution described in any one of claims 1-6, and transport it to a raw foil machine for electrolytic foil production; during electrolysis, the concentration of Cu in the electrolyte solution 2+ is 80-110 g / L.

8. The preparation method of the electrolytic copper foil for lithium batteries according to claim 7, characterized in that, The temperature of the electrolyte is 50 - 65 °C.

9. The preparation method of the electrolytic copper foil for lithium batteries according to claim 7, characterized in that, The flow rate of the conveying is 50 - 70 m 3 / h.

10. The preparation method of the electrolytic copper foil for lithium batteries according to claim 7, characterized in that, The current density of the electrolysis is 3600 - 6000 A / m 2 .

Citation Information

Patent Citations

  • Electrolytic copper foil for lithium battery and preparation method and application thereof

    CN118292056B

  • Preparation method of ultra-thin electrolytic copper foil for general-strength lithium ion battery

    CN111172567A

  • Additive suitable for stably improving elongation rate of common-resistance 8-micron lithium battery copper foil and use method of additive

    CN114086219A

  • Lithium battery copper foil collagen-free composite copper plating additive and application thereof

    CN115449857A

  • Acidic bright copper plating electroplating solution as well as preparation method and application thereof

    CN116590764A